Plants species as feed sources and nesting site of cuscus (Family Phalangeridae) in Northern Biak Nature Reserve, Papua - HADI DAHRUDDIN; WARTIKA ROSA FARIDA; AEP SYAEPUL ROHMAN (Biodiversitas Journal of Biological Diversity, 2005)
Studies on nesting site and feed selection of cuscus in Northern Biak Nature Reserve, Biak Numfor level two district, Papua was conducted from August to September 2003. The result showed 57 species of plant used as cuscus feed sources and 11 species of plants as their nesting site. Parts of the plants being consumed were fruit (76,1%), leaves (13,4%), flowers (9%), and shoot (1,5%). The night watched identified two species of cuscus, namely common cuscus (Phalanger orientalis Pallas), and spotted cuscus (Spilocuscus maculatus Desmarest). Direct threat for their conservation were due to hunting pressure by outer conservation area people, specially Biak city people, as just for laugh.Key words: Cuscus, family Phalangeridae, feed sources, nesting site, Northern Biak Nature Reserve